2013
DOI: 10.1371/journal.pone.0080438
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Annual Diving Behaviour by Hooded Seals (Cystophora cristata) within the Northwest Atlantic Ocean

Abstract: With the exception of relatively brief periods when they reproduce and moult, hooded seals, Cystophora cristata, spend most of the year in the open ocean where they undergo feeding migrations to either recover or prepare for the next fasting period. Valuable insights into habitat use and diving behaviour during these periods have been obtained by attaching Satellite Relay Data Loggers (SRDLs) to 51 Northwest (NW) Atlantic hooded seals (33 females and 18 males) during ice-bound fasting periods (2004−2008). Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 65 publications
2
31
0
Order By: Relevance
“…Due to the larger size of males, it is expected that they need to feed more than females if they are foraging on similar prey [15]. Although the drift dive frequencies were similar directly after breeding, males have previously been found to perform slightly longer and deeper dives than females during the same time period (see [44]). Our habitat model also showed that male and female NW Atlantic hooded seals have different movement patterns, using different geographical areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the larger size of males, it is expected that they need to feed more than females if they are foraging on similar prey [15]. Although the drift dive frequencies were similar directly after breeding, males have previously been found to perform slightly longer and deeper dives than females during the same time period (see [44]). Our habitat model also showed that male and female NW Atlantic hooded seals have different movement patterns, using different geographical areas.…”
Section: Discussionmentioning
confidence: 99%
“…Andersen et al [44] used First Passage Time (FPT, see [45]) and three habitat variables (geographic location, bottom depth and the Topographic Complexity Index (TCI) to identify such areas based on data from the same dataset as used in this study. FPT is defined as the time an animal uses to cross a circle of a given radius [45], of which the scale of the circle is determined by calculating the animals' average Area Restricted Search (ARS) scale (see [46]).…”
Section: Introductionmentioning
confidence: 99%
“…Gregr 2011, Roberts et al 2016 (Table 1): (1) ocean depth (Fig. 2); (2) compound topographic index (CTI) -derived from ocean depth (Evans et al 2014), this variable re flects the peaks (high numeric values of CTI), basins (low values), and flat surfaces (intermediate values) of the ocean floor (Moore et al 1991, Gessler et al 1995, Andersen et al 2013 (Fig. 2); (3) sea surface temperature (SST) -average summer water temperature close to the ocean's surface (Fig.…”
Section: Environmental Datamentioning
confidence: 99%
“…Hidden Markov model [58,59], first passage time [60], state space model [61,62]) and used to relate the defined horizontal ARS to particular structures of the environment (e.g. oceanographic features [31,53,63], sea ice [64,65], topography [66,67]). Bailleul et al [36] underlined the importance of integrating a vertical index of foraging effort to better identify foraging areas when studying deep-diving marine predators.…”
Section: Ecological Applicationsmentioning
confidence: 99%